Optimal Hysteresis Model Parameters for the Seismic Response of Reinforced Concrete - Lepage, Andrés; Delgado, Sebastián A. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This work seeks to identify the optimal combination of parameters defining the hysteretic response of reinforced concrete frames and leading to the best correlation between the calculated and measured seismic response. The combined effects of five parameters are investigated: initial stiffness, bond-slip deformations, post-yield stiffness, unloading stiffness, and type of damping. The analyses use lumped plasticity models concentrated at member ends. The study uses the recorded seismic responses of two ten-story laboratory structures and two orthogonal structural systems in an existing seven-story building. For each of the four structures, 64 combinations of parameters are considered for a total of 256 cases. For each case, the calculated roof displacement is compared to the measured response by means of the frequency domain error index (FDE), facilitating the identification of the combination of parameters that leads to the best analytical simulation to minimize FDE. Although the best simulations are attained in models with uncracked initial stiffness, hard post-yield stiffness, and variable unloading stiffness, the study identifies models with cracked initial stiffness that also lead to satisfactory simulations.